Boosting agro-processing industry in India - Manjunath, B L; Narayana, C K (Indian Farming, 2021)
India has the second-largest arable land resources in the world, with 20 agri-climatic regions. India is also the largest producer of spices, pulses, milk, tea, cashew, and jute, and the second largest producer of wheat, rice, fruits and vegetables, sugarcane, cotton, and oilseeds. Paradoxically, though India is one of the largest food crops producer in the world, the level of processing is low. Lack of adequate process-able varieties is said to be one of the reasons for low level of processing. However, realizing the fact that no single cause can be attributed as the reason, the government has introduced several schemes and modernization initiatives to improve the agro-processing in the country. As part of the approach, efforts have been made to increase digital transactions, cutting red tape, increasing efficiency, ease of doing business, unification of multiple taxes and several others like Operation Green, PMFME, NMFP, etc.